DEVELOPMENT OF A PROTOCOL FOR MICROCLONAL PROPAGATION OF PISTACIA VERA L. (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Kyrgyzstan and Kazakhstan are characterised by a predominance of arid lands. In such regions, the cultivation of drought-resistant crops is particularly important. One such crop is the pistachio (Pistacia vera L.). It grows in these territories and is of high ecological and economic importance. Microclonal propagation is the most effective method for large-scale production of planting material. The primary material for developing the microclonal propagation protocol was green, actively growing pistachio cuttings with 2-3 buds. A total of 20 forms of true pistachio were introduced. Sterilisation from saprophytic microflora was carried out with a solution of “Bleach” (1:1) for 10 minutes and a 0.1% solution of HgCl₂ for 5 minutes, after which the material was rinsed three times with sterile distilled water. The best results of microclonal propagation were achieved on Murashige and Skoog medium supplemented with 1.0 mg/L 6-benzylaminopurine (BAP) and 0.02 mg/L indole-3-butyric acid (IBA). The data obtained are important for preserving the gene pool and obtaining high-quality planting material of Pistacia vera.
Keywords: pistachio, aseptic plants, microclonal propagation, in vitro, green shoots, sterilisation